Infective Endocarditis Caused by C. sordellii: The First Case Report from India - Chaudhry, Rama; Bahadur, Tej; Sagar, Tanu; Agrawal, Sonu Kumari; Arif, Nazneen; Choudhary, Shiv K.; Verma, Nishant (Journal of Laboratory Physicians, 2021)
Clostridium sordellii is a gram-positive anaerobic bacteria most commonly isolated from skin and soft tissue infection, penetrating injurious and intravenous drug abusers. The exotoxins produced by the bacteria are associated with toxic shock syndrome. We report here a first case of infective endocarditis due to C. sordellii from a female patient with ventricular septal defect from India.
Keywords: infective endocarditis; Clostridium sordellii; diagnosis